(untitled) (REMUNOM, 2023)
This study aims to address the diagnosis of the consumer profile of pork in the municipality of Guaraí, Tocantins, regarding choice factors, frequency, preference, quantity consumed, consumption of derivatives, and other sources of animal protein consumed. The diagnosis was carried out through interviews with online forms. It was found that, in the municipality of Guaraí-TO, the consumption of pork remains relatively low, with beef being the predominant preference among respondents. Pork, on the other hand, is less sought after and faces limited availability, resulting in reduced interest among consumers. In this context, the need to improve the marketing of this product and raise awareness among consumers about the nutritional value of pork becomes evident.